Differential expression of microRNAs in 2-cell and 4-cell mouse embryos. Issue 4 (November 2014) - Wang, Pei; Cui, Ji; Zhao, Chun; Zhou, Lin; Guo, Xirong; Shen, Rong; Zhang, Junqiang; Ling, Xiufeng
Summary In vitro fertilized (IVF) human embryos have a high incidence of developmental arrest before the blastocyst stage, therefore characterization of the molecular mechanisms that regulate embryo development is urgently required. Post-transcriptional control by microRNAs (miRNAs) is one of the most investigated RNA control mechanisms, and is hypothesized to be involved actively in developmental arrest in preimplantation embryos. In this study, we extracted total RNA from mouse 2-cell and 4-cell embryos. Using a miRNA microarray, 192 miRNAs were found to be differentially expressed in 4-cell embryos and 2-cell embryos; 122 miRNAs were upregulated and 70 were downregulated in 4-cell embryos. The microarray results were confirmed by real-time quantitative RT-PCR for six miRNAs (mmu-miR-467h, mmu-miR-466d-3p, mmu-miR-292–5p, mmu-miR-154, mmu-miR-2145, and mmu-miR-706). Cdca4 and Tcf12 were identified as miR-154 target genes by target prediction analysis. This study provides a developmental map for a large number of miRNAs in 2-cell and 4-cell embryos. The function of these miRNAs and the mechanisms by which they modulate embryonic developmental arrest require further study. The results of this study have potential applications in the field of reproductive medicine.